Low-Dimensional Transition Metal Dichalcogenide Nanostructures Based Sensors - Li, Bang Lin; Wang, Jinping; Zou, Hao Lin; Garaj, Slaven; Lim, Chwee Teck; Xie, Jianping; Li, Nian Bing; Leong, David Tai (Advanced functional materials, 2016)
Two‐dimensional (2D) transition metal dichalcogenides (TMDs) nanostructures have been widely applied in environmental and biological analysis, biomedicine, electronic devices, and hydrogen evolution catalysis. Meanwhile, this excitement in 2D TMDs has spilled over to their counterparts of different dimensionalities like one‐dimensional (1D) and zero‐dimensional (0D) TMDs nanostructures. Eventual physical and chemical properties of TMDs nanostructures still remain to be highly dependent on their dimensionalities and size scale, and recently creatively exploring these physical and chemical properties is extremely impactful for the sensing field of TMD nanomaterials. Herein, we review a wide range of sensing applications based on not only graphene‐like 2D TMDs nanostructures but also the rapidly emerging subclasses of 1D, and 0D TMDs nanostructures. Their unique and interesting structures, excellent properties, and valid preparation methods are also included and the analytical objectives, ranging from heavy metal ions to small molecules, from DNA to proteins, from liquids to even vapors, can be met with extremely high selectivity and sensitivity. We have also analyzed our current understanding of 0D and 1D TMDs nanostructures and learning from graphene with the goal of contributing fresh ideas to the overall development of more advanced future TMDs based sensors. Sensing applications of transition metal dichalcogenides (TMDs) nanostructures (2D, 1D, and 0D morphologies) are systematically presented with their unique structures, distinct properties, and preparation methods. Due to their interesting and useful electronic, optical, and catalytic properties, TMDs nanostructures can be good alternatives to the popular graphene nanomaterials in building advanced sensors.